Integrated environmental protection biofeedback game (IEPBG) using galvanic skin response (GSR) sensor - Kwee Ming, Chang (2012)
The purpose of this project is to develop the application called Integrated Environmental Protection Biofeedback Game (IEPBG) Using Galvanic Skin Response (GSR) Sensor, which is a biofeedback game that gives awareness about the environmental protection issues. A biofeedback game is built due to the several approaches to environmental protection that are currently discussing. The concept of reduce, reuse, and recycle (3R) approaches is interrelated to the ecosystem approaches. The biofeedback game engage out emotion on a moment-by-moment basis, and using those emotions as an input gives games the potential for more dynamic and immersive environments. IEPBG is a game which integrated with the galvanic skin response (GSR) sensor. GSR sensor is use to detect the skin conductance level (SCL) while the players play this biofeedback game. The prototype of the IEPBG using GSR sensor is suitable for all human in order to do as an emotion application while integrates with the GSR sensor. It will help the players to view the SCL activity report. Through the development of this game, it shows the result with when the arousal is high, the awareness environmental protection will high. While the arousal of the player is low, the weak of the awareness on environmental protection.